EFEK REBUSAN DAUN SELEDRI TERHADAP PENURUNAN KADAR ASAM URAT - Maryuni, Sri; Astuti, Vidya Dwi; Sari, Eva Karmila (Coping: Community of Publishing in Nursing; Vol 11 No 3 (2023): Juni 2023DO - 10.24843/coping.2023.v11.i03.p02, 2023)
Gout arthritis is caused by exercessive production of uric acid and decreased excretion, resulting in painful symptoms. One non-pharmacological approach in treating gout is the administration of boiled celery leaves. This objective of this research it to determine the effect of celery leaf decoction (Apium graveolens L.) on uric acid levels among the population in the working area of the UPTD Tanjung Sari Health Center, Natar District, South Lampung Regency in 2022. This research method employed is a quantitative quasi-experimental design with a pretest and posttest with a control group design . The study population consists of individuals who have experienced gout within the working area of the UPTD Tanjung Sari Health Center, Natar District, South Lampung Regency from Januari to March 2022. A total of 40 respondents participated, with 20 in the interventation group and 20 in the control group. Based on statistical analysis, a p-value of 0,000 or p-value < 0,05 was found, indicating the implications of providing celery leaf decoction on uric acid levels among the population in the working area of the Tanjung Sari Health Center, South Lampung Regency, in 2022.